Modelling Escherichia coli adsorption in selected soils in Sarawak - Goh, Soon Hian. (2006)
One major impact of animal farming activities is the non-point source microbial pollution of waterways. Manure from animal feeding operations can be a potential source of fecal bacteria, including various types of fecal pathogens. In this study, adsorption of fecal bacteria in 5 different soils was investigated. Escherichia coli (wild strains) isolated from animal wastewater was used as an indicator of microbial pollution of water in the study.